S57 Predicting outcome from exacerbations of copd requiring assisted ventilation: results from the NIV Outcome (NIVO) study. (12th November 2019) - Hartley, TM; Lane, ND; Steer, J; Elliott, MW; Sovani, M; Curtis, HJ; Fuller, ER; Murphy, PB; Hart, N; Shrikrishna, D; Lewis, KE; Ward, NR; et al.
Abstract : Introduction: Exacerbations of COPD account for approximately 12% of UK hospital admissions. Over 20% will be complicated by respiratory acidaemia, which has high mortality. Non-Invasive ventilation (NIV) confers a 2–3 fold mortality reduction, but practice is sub-optimal; the intervention is underused, infrastructure is lacking, and complex decisions are made by a wide range of clinicians. 1 It is likely that prognostic pessimism contributes to underuse. We aimed to derive and separately validate a simple, bedside, clinical tool to predict in-hospital mortality in exacerbations of COPD complicated by respiratory acidaemia requiring assisted ventilation. Methods: Derivation was single-centre and retrospective. Consecutive patients meeting selection criteria were identified and clinical data collected. Multivariable regression identified independent predictors of in-hospital death and a simple model created. For validation, consecutive patients were prospectively recruited from 10 sites and model performance assessed. Results: 489 patients were identified in the derivation study and 733 in the validation (in-hospital mortality 25.4 and 20.1% respectively). Key validation descriptors: 70% hospitalised during previous year, Mean (SD) age 70.5 (9.3) years and FEV1 % predicted 37.2 (15.4). 56% were unable to leave the house unassisted (eMRCD 5a or 5b) and 29% prescribed LTOT. 36% had previously required NIV and 9% were receiving home ventilation. Median (IQR) pH at onset of ventilation 7.27 (7.22–7.30), with CO2 10.2 (2.7) kPa. The final prognostic (NIVO) score comprised: Atrial fibrillation, chest X-ray consolidation, pH <7.25, Glasgow coma scale ≤14 (all 1 point), timing of acidaemia >12 hours from admission time (2 points) and eMRCD (1– 4=0, 5a=2, 5b=3) yielding a maximum score of 9 using 6 indices. Stepwise increase in mortality was observed with an area under the receiver operated curve of 0.79 in the validation cohort (0.83 derivation). The NIVO score outperformed pre-identified comparator scores (APACHE II, CAPS, Confalonieri risk chart) in both its derivation and validation studies. Discussion: Using only simple, readily available indices good prediction of in-hospital mortality is feasible. Potential practical applications include but are not limited to guiding level of care, setting treatment limitations and objectifying both clinician decision making and discussion with patients/family members. Reference: Inspiring change 2017